BEST‐TEST2: assessment of hematology trainee knowledge of transfusion medicine. Issue 2 (24th September 2015) - Lin, Yulia; Tinmouth, Alan; Mallick, Ranjeeta; Haspel, Richard L.
Abstract : BACKGROUND: As transfusion is a common therapy and key component in every hematologist's practice, hematology training programs should dedicate significant time and effort to delivering high‐quality transfusion medicine education to their trainees. The current state of hematology trainee knowledge of transfusion medicine is not known. STUDY DESIGN AND METHODS: A validated assessment tool developed by the Biomedical Excellence for Safer Transfusion (BEST) Collaborative was used to assess prior transfusion medicine education, attitudes, perceived ability, and transfusion medicine knowledge of hematology trainees. RESULTS: A total of 149 hematology trainees at 17 international sites were assessed. The overall mean exam score was 61.6% (standard deviation, 13.4%; range, 30%‐100%) with no correlation in exam scores with postgraduate year or previous transfusion medicine education in medical school or internal medicine residency. However, better scores correlated with 3 or more hours of transfusion medicine education (p = 0.0003) and perceived higher‐quality education during hematology training (p = 0.03). Hematology trainees at US sites, where hematology is often combined with oncology training, had statistically lower scores than trainees at non‐US sites (56.2% vs. 67.4%; p < 0.0001). In terms of topic areas, although 93% of participants had obtained consent for transfusion, the lowest scores were on transfusion reaction–related questions. CONCLUSION: Given the overall poor performance, this study serves as an impetus for all hematology training programs to reevaluate the quality and quantity of transfusion medicine training and can assist in the development of targeted curricula.